2019
DOI: 10.1186/s12939-019-1055-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV prevalence in South Africa through gender and racial lenses: results from the 2012 population-based national household survey

Abstract: BackgroundIn South Africa, persistence of the HIV epidemic and associated gender and racial disparities is a major concern after more than 20 years of democratic dispensation and efforts to create a more healthy and equal society. This paper profiles HIV prevalence and related factors among Black African men and women compared to other race groups in South Africa using the 2012 population-based national household HIV survey.MethodsThis secondary data analysis was based on the 2012 population-based nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 31 publications
9
49
0
1
Order By: Relevance
“…It is also possible some people knew their status as negative and that they had no reason to use a condom especially when they were sure of the negative status of their partners. This finding was consistent with a previous study that found HIV prevalence to be significantly higher among those who reported using a condom at last sex compared to those who reported not using a condom [37], and our explanation could be true in this study, too. We also found that persons who used condom for their most recent sex were more likely to test positive for HIV.…”
Section: Plos Onesupporting
confidence: 93%
“…It is also possible some people knew their status as negative and that they had no reason to use a condom especially when they were sure of the negative status of their partners. This finding was consistent with a previous study that found HIV prevalence to be significantly higher among those who reported using a condom at last sex compared to those who reported not using a condom [37], and our explanation could be true in this study, too. We also found that persons who used condom for their most recent sex were more likely to test positive for HIV.…”
Section: Plos Onesupporting
confidence: 93%
“…Although great strides have been made in the management of the HIV pandemic in South Africa, HIV-related stigma PLOS ONE continue to be serious barriers to HIV testing, prevention, access to treatment and care for PLHIV, and the mitigation of impact of the disease. Importantly, South Africa is home to the largest population of PLHIV [52]. Historically, the AIDS denialism discourse (of beetroot, garlic and lemon) [53] that characterised the HIV pandemic in South Africa was further complicated by an othering of blame for the transmission of the disease premised on racism, patriarchy and homophobia [33].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of 2020, the Joint United Nations Program on HIV/AIDS (UNAIDS) estimates there are 38 million people living with HIV/AIDS worldwide. Despite new HIV-1 infections having been reduced by 23% since 2010, Sub-Saharan Africa remains the most affected region, accounting for an estimated 69% of all people living with HIV/AIDS, where gender-based violence and inequalities continue to drive the epidemic [ 1 , 2 , 4 , 5 , 6 ]. In African countries, 25.7 million people are infected with HIV-1, which also accounts for almost two-thirds of the global total of new HIV-1 infections.…”
Section: Introductionmentioning
confidence: 99%